Knowledge and perception regarding personal protection equipment and infection control measures against COVID-19 among dental practitioners of Saudi Arabia - Saeed Ali Alqahtani; Mashael Obaid Alshahrani; Mona Oweidh Alnefaie; Abdullah Mana Almofrej; Fahad Hassan Aldaghsh; Nasser Saad Alamri; Sultan Saleh Alshamrani (Wolters Kluwer Medknow Publications, 2021)
Introduction: The lack of interest and knowledge related to personal protection equipment (PPE) and infection control measures might have a detrimental effect on dental occupational workers. Aim: The purpose of this study was to evaluate the knowledge and perception of dental practitioners about PPE to limit the spread of coronavirus disease 2019 (COVID-19). Materials and Methods: This cross-sectional descriptive study was conducted between May and June 2020 among the dental practitioners working in public and private sectors of Saudi Arabia. An online questionnaire was distributed among dental practitioners across Saudi Arabia using E-mails or WhatsApp software. The questionnaire consisted of two parts: (1) basic demographic characteristics (gender, professional status, type of dental setup, and working experience) and (2) knowledge and attitude regarding the use of a face mask, gloves, gowns, and personal hygiene. Descriptive statistics were performed to summarize frequencies and percentages. Results and Discussion: The total number of the responses received was 535 (68.8% - male and 31.2% - female). Only 17.8% knew that surgical masks are made of nonwoven fabric and that the middle layer acts as a barrier (39.8%). Regarding gloves, 57.4% of the participants agreed that latex/nitrile gloves are more reliable and durable. On the contrary, satisfactory knowledge regarding face shield, gown, hand hygiene, and infection control measures was observed. Conclusions: This study showed a low level of certain PPE knowledge among dental practitioners. However, knowledge and perception about biosafety, face shield, gown, hand hygiene, and infection control measures were found to be higher and adequate among the participants.